О ЖАНРОВОЙ СПЕЦИФИКЕ ТЕКСТОВ ЦЕРКОВНО-РЕЛИГИОЗНОГО СТИЛЯ (Филолошки студии, 2019)
The article discusses the features of genre organization of the church-religious style the Russian. The genre models are described from the point of view of the spiritual activity in religious field. In this connection it is proposed to consider not only central genres those are a prayer, a sermon and a confession, but also to consider peripheral genres associated with specific firmness of purpose appropriate to Orthodox church-religious discourse. Hence it is studied the regulating (official), preceptoring, theological genres and genres of expressions of the individual faith. For the investigation of genre character of church-religious texts is suggested to introduce a notion of “metagenre” implying a general stylistic-neutral unfilled abstract model connected with firmness of purpose of speech activity. Thus the statute genre with respect to specific genres of monastic and secular statutes obviously is metagenre. For grading church-religious genres have been used institutive, subjective and intensional scales.